Sales and Purchase Agreement As The Basis of Land Ownership Transfer Registration In The Context of Tax Amnesty - Erika Lierensia (Faculty of Law, Merdeka University Surabaya, Indonesia, 2019)
In 2016, the President of the Republic of Indonesia legislated the Law of the Republic of Indonesia Number 11 of 2016 on Tax Amnesty. One of the regulated policies is that assets that are still registered in the name of another person and have not been disclosed by the Taxpayer must be disclosed and transferred into the name of the Taxpayer with the exemption of income tax imposition. With this provision, the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Released the regulation Number 15 of 2017 concerning the Registration of Transfers on Land Rights in the Framework of Tax Amnesty, and followed up with the issuance of the Circular Announcement Number 9/SE/X/2017 concerning the Implementation Guidelines of the Regulation of the Minister of Agrarian and Spatial Planning/Head of National Land Agency Number 15 of 2017 concerning Registration of Transition of Land Rights in the Context of Tax Amnesty. This Circular Announcement stipulates that the registration of the transfer of land rights is executed by making a nominee statement letter between the Taxpayer and the Nominee, and if previously the nominee statement letter has not been made but a legal act has been carried out, then the party can use the deed of binding and transfer ownership of rights of the land or apartment that are made by a Notary. The agreement of the transfer ownership of land or the apartment unit referred to is the Agreement on the Binding of Sale and Purchase. With this provision, the registration of the transfer of rights of the land is possible on the basis of the Agreement on the Binding of Sale and Purchase whereas the Agreement is a pledge between the prospective seller and the prospective buyer to transfer the rights of ownership of the land at an agreed price.